Recreational-cultural leisure and intergenerational relationship - Valdemoros San Emeterio, María Ángeles; Sáenz De Jubera Ocón, Magdalena; Alonso Ruiz, Rosa Ana; Medrano Pascual, Cristina; Santamaría Baños, Mario (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The aim of this study was to examine the recreational and cultural leisure shared between grandparents and grandchildren and its impact on the relation and communication of both generations. Both quantitative -ad hoc questionnaire administered to 1080 primary students- and qualitative -two discussion groups with categories validated with Cohen’s Kappa- techniques were used. The investigation was carried out in the North of Spain with children between 6 and 12 years old and the presence of recreational and cultural activities enhances the improvement of their emotional bond. Increases in communication, amusement, mutual learning and emotional well-being are highlighted as main contributions. Recreational and cultural leisure in intergenerational contexts was positively associated with a better relationship between grandparents-grandchildren and was considered an enabling factor for the intergenerational communication.